Can anti-osteoporotic therapy reduce adjacent fracture in magnetic resonance imaging-proven acute osteoporotic vertebral fractures?. Issue 1 (December 2016) - Chen, Ying-Chou; Lin, Wei-Che
Abstract Background Adjacent fracture of the cemented vertebrae result from crushed fragile trabeculae during follow-up, suggesting impaired bone marrow integrity. This study aimed to determine if anti-osteoporotic therapy can decrease the risk of adjacent fracture in patients after vertebroplasty. Methods This retrospective study reviewed of cases of osteoporotic patients with magnetic resonance imaging (MRI)-proven acute vertebral fractures between 2001 and 2007. Osteoporotic patients were investigated as determined by pre-operative MRI with subsequent adjacent fracture of the cemented vertebrae and for the possibility of anti-osteoporotic therapy decreasing the progression of collapse after a minimum of 6 months follow-up. All associated co-morbidities were recorded, as well as the use of anti-osteoporotic drugs (i.e., bisphosphonate, raloxifen, calcitonin, and teriparatide). Cox regression analysis was also performed. Results The 192 vertebral fractured patients who underwent vertebroplasty and anti-osteoporotic therapy had a mean age of 74.40 ± 6.41. The basic characteristics of patients with and without adjacent fracture differed in age, body mass index, rheumatoid arthritis, and use of glucocorticoids and anti-osteoporotic drugs (Table 1). Using the Kaplan-Meier curve, anti-osteoporotic therapy after vertebroplasty had a significant effect on adjacent fracture (p  = 0.037, by log rank text). After adjusting for potential confounders, patients with anti-osteoporotic therapy still had a lower adjacent fracture rate than patients without anti-osteoporotic therapy (p  = 0.006; HR: 2.137, 95 % CI: 1.1238–3.690). The adjacent fracture rate also increased in old age (p  = 0.019; HR: 1.049; 95 % CI:1.008–1.039) and among smokers (p  = 0.026; HR: 3.891; 95 % CI: 1.175–12.890). Conclusions In this study, adjacent fracture of cemented vertebrae is inevitable after vertebroplasty but can be mitigated by anti-osteoporotic therapy to increase bone mass.